The family therapy progress notes planner - Berghuis, David J.; Jongsma, Arthur E., 1943- (Hoboken, N.J. : John Wiley & Sons, 2010)
'Progress notes allow therapists to document the therapeutic process and are one of the main factors in determining reimbursable treatment. Fully updated and revised, this book contains complete prewritten session and patient presentation descriptions for each behavioral problem in The Family Therapy Treatment Planner, Second Edition (ISBN 978-0-470-44193-0). The prewritten progress notes can be easily and quickly adapted to fit a particular client need or treatment situation and contain language consistent with evidence-based treatment interventions. Up-to-date and easy-to-use, this book saves marriage and family therapists hours of time-consuming paperwork.'--Provided by publisher
Machine generated contents note: PracticePlanner Series Preface. -- Acknowledgements. -- Introduction. -- Activity/Family Imbalance. -- Adolescent/Parent Conflicts. -- Adoption Issues. -- Alcohol Abuse. -- Anger Management. -- Anxiety. -- Blame. -- Blended Family Problems. -- Child/Parent Conflicts. -- Communication. -- Compulsive Behaviors. -- Death of a Child. -- Death of a Parent. -- Dependency Issues. -- Depression in Family Members. -- Disengagement/Loss of Family Cohesion. -- Eating Disorder. -- Extrafamilial Sexual Abuse. -- Family Activity Disputes. -- Family Business Conflicts. -- Family Member Separation. -- Family-of-Origin Interference. -- Financial Changes. -- Geographic Relocation. -- Incest Survivor. -- Infidelity. -- Inheritance Disputes between Siblings. -- Interfamilial Disputes Over Wills and Inheritance Interracial Family. -- Problems Intolerance/Defensiveness Jealousy/Insecurity Life. -- Threatening/Chronic Illness Multiple Birth Dilemmas Physical/Verbal. -- Psychological Abuse Religious/Spiritual Conflicts Reuniting Estranged. -- Family Members Separation/Divorce Sexual Orientation Conflicts Traumatic. -- Life Events Unwanted/Unplanned Pregnancy
Keywords: Family Therapy -- methods -- Handbooks; Medical Records -- Handbooks; Patient Care Planning -- handbooks